THE PEDAGOGICAL MODEL OF TEACHER TRAINING AS AN EFFECTIVE MEANS OF ONLINE TEACHER TRAINING - Topuzyan A.O.,; Durgaryan A.M., (International Journal of Innovative Technologies in Social Science, 2024)
The socio-economic situation created in the country today requires new ways and approaches in order to improve the quality of education and raise the qualifications of teachers in the field of milking, which include not only the problems of teacher training and the features of the training process, but also put forward and consider its features with modern technologies. Today, a completely different new field has its unique place and influence in teacher training: media literacy, which allows the process of teacher training to be transferred from a face-to-face platform to an online platform, changing not only the forms and process of its organization, but also the role and significance of training. in action. By being trained from this point of view, the teacher acquires not only new theoretical and practical knowledge, but also skills and abilities to use modern technologies.